PENGARUH KONDISI KEUANGAN, KUALITAS AUDIT, DEBT DEFAULT, FIRM SIZE, DAN AUDIT LAG TERHADAP OPINI AUDIT GOING CONCERN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2020) - Indri Rahmawati; Darsono Darsono (Diponegoro Journal of Accounting, 2022)
This research aims to test the influence of financial conditions, audit quality, debt default, firm size and audit lag on audit opinion going concerns in manufacturing companies The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2019-2020. The purposive sampling method is used as a sampling method with certain criteria with a total sample of 277 samples. Based on the results of the study showed that variable financial conditions and audit lag had an significant positive effect on the opinion of audit going concern. The firm size variable had a significant negative effect on the audit of opinion going concern. The acquisition of audit quality variables has a insignificant negative effect on the opinion of audit going concern. The test results also showed that the default debt variable had an insignificant positive effect on the audit opinion going concern.